1976
DOI: 10.1136/thx.31.6.736
|View full text |Cite
|
Sign up to set email alerts
|

Transitory cerebral microvascular blockade after cardiopulmonary bypass.

Abstract: . (1976). Thorax, 31,[736][737][738][739][740][741]. Transitory cerebral microvascular blockade after cardiopulmonary bypass. Dogs were submitted to cardiopulmonary bypass (CPB) carried out under conditions calculated to generate large numbers of microbubbles and microemboli. On the day following the procedure the dogs showed evidence of neurological damage including impaired consciousness and ataxia. These abnormalities largely cleared within a week. When the animals were sacrificed at intervals after the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…16,20 The rapid decline in microemboli found in this study is consistent with observations in dogs showing that after CPB, most microvascular occlusions had disappeared within 7 days, 32,33 and with the observations of Blauth et al 34 that vascular occlusions in the retinas of CPB patients were more numerous during CPB than after CPB.…”
Section: Discussionsupporting
confidence: 81%
“…16,20 The rapid decline in microemboli found in this study is consistent with observations in dogs showing that after CPB, most microvascular occlusions had disappeared within 7 days, 32,33 and with the observations of Blauth et al 34 that vascular occlusions in the retinas of CPB patients were more numerous during CPB than after CPB.…”
Section: Discussionsupporting
confidence: 81%
“…Activation of the complement system with disruption of cell membranes may occur as a result of CPB. , [6][7][8][9][10][11][12][13][14][15][16][17][18][19] In a group of dogs undergoing hypothermic CPB, Johnston et al , 4 found that cerebral blood flow (CBF) was markedly reduced during 150 min of hypothermic CPB and remained so even after rewarming. They saw a small, but significant, rise in intracranial pressure (ICP) but could demonstrate no evidence of brain oedema on the basis of cerebral water content.…”
Section: Discussionmentioning
confidence: 99%
“…This fall was abolished in filtered CPB, and Doppler counting confirmed the efficacy of the filter in reducing bubble exposure. Patterson et al (61) subjected dogs to 2 hours of CPB using a bubble oxygenator operated in such a way as to produce numerous microbubbles. Groups of dogs were sacrificed after progressively longer periods of recovery.…”
Section: Pathophysiological Significance Of Cage In Cardiac Surgerymentioning
confidence: 99%